Nilai - Nilai dalam Upacara Penti di Manggarai Ditinjau dari Perspektif Filsafat Moral Kant - Atu, Laurentius Florido; Koten, Yohanes Gekeng (Proceedings of The National Conference on Indonesian Philosophy and Theology, 2024)
Each culture has various traditional ceremonies. Traditional ceremonies become one of the entities that perpetuate a culture. Each traditional ceremony has values that want to be preserved and taught to the followers of that culture. The Penti Ceremony in the Manggarai Community, Flores, NTT is one of the pedagogical cultural activities. There are many values to be taught in the ceremony. Therefore, this paper aims to examine the important values contained in the Penti ceremony from the perspective of Immanuel Kant's moral philosophy. This research uses a qualitative approach with ethnographic methods. The results of this study show that the Penti ceremony contains philosophical values that can be interpreted from the perspective of Kant's moral philosophy, such as harmony with God and others. These positive things are important to be raised in order to become material that can be taught to the younger generation through formal and informal schools, such as local content programs.AbstrakSetiap budaya memiliki aneka upacara adat. Upacara adat menjadi salah satu entitas yang melanggengkan sebuah kebudayaan. Masing-masing upacara adat memiliki nilai-nilai yang hendak dilestarikan dan diajarkan kepada para penganut budaya tersebut. Upacara Penti dalam Masyarakat Manggarai, Flores, NTT adalah salah satu kegiatan kebudayaan yang berdaya pedagogis. Ada banyak nilai yang hendak diajarkan dalam upacara tersebut. Oleh karena itu, tulisan ini bertujuan untuk mengkaji nilai-nilai penting yang terkandung dalam upacara Penti ditinjau dari perspektif filsafat moral Immanuel Kant. Penelitian ini menggunakan pendekatan kualitatif dengan metode etnografi. Hasil dari studi ini menunjukkan bahwa upacara Penti  mengandung nilai-nilai filosofis yang dapat dimaknai dari perspektif filsafat moral Kant, seperti  keharmonisan dengan Tuhan dan sesama. Hal-hal positif ini penting diangkat guna menjadi bahan yang bisa diajarkan kepada generasi muda melalui  sekolah-sekolah formal dan informal, misalnya program muatan lokal.